2018
DOI: 10.4274/tjod.57255
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the diabetes in pregnancy study group of India criteria and Carpenter-Coustan criteria in the diagnosis of gestational diabetes mellitus

Abstract: Objective:Gestational diabetes mellitus (GDM) is defined as any degree of glucose intolerance that is diagnosed for the first time during pregnancy. This prospective study was undertaken to validate the single-step non-fasting 75 gm Diabetes in Pregnancy Study Group of India (DIPSI) criteria of GDM in Indian patients in comparison with the two-step fasting 100 gm glucose challenge through the Carpenter Coustan criteria (CCC).Materials and Methods:Two hundred patients underwent comparative testing using the DIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 24 publications
0
18
0
1
Order By: Relevance
“…Of 286 studies found, 21 studies [ 14 , 16 , 33 51 ] met the criteria, but the data of 2 studies [ 36 , 44 ] were insufficient to be extracted resulting in a total of 19 studies [ 14 , 16 , 33 35 , 37 – 43 , 45 51 ] being included in the quantitative analyses. The flow chart of literature screening and selection process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of 286 studies found, 21 studies [ 14 , 16 , 33 51 ] met the criteria, but the data of 2 studies [ 36 , 44 ] were insufficient to be extracted resulting in a total of 19 studies [ 14 , 16 , 33 35 , 37 – 43 , 45 51 ] being included in the quantitative analyses. The flow chart of literature screening and selection process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…More than half were at low risk of bias and low applicability concerns in all domains. Of the 21 studies, [ 14 , 16 , 33 51 ] 14 studies [ 14 , 16 , 33 , 37 – 40 , 43 , 44 , 46 , 48 51 ] were at low risk of bias for participant selection and 7 studies [ 34 – 36 , 41 , 42 , 45 , 47 ] were at unclear risk of bias due to insufficient information of exclusion criteria. High applicability concerns of patient selection were found in four studies [ 33 , 34 , 36 , 41 ] because only women having positive index tests were tested with a reference test.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucose in the blood is called blood sugar. The operation of various tissues and organs of the body requires glucose to provide energy (20). The normal body maintains blood glucose at a relatively stable level through hormonal regulation and nerve regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Timely revealing of glucose intolerance in pregnancy offers an opportunity for screening, management and prevention of GDM on time and prevents fetal complications thus improves neonatal outcomes [6,7]. This necessitates the general mandatory screening for GDM during pregnancy, which is a resource intensive testing modality.…”
Section: Introductionmentioning
confidence: 99%